2013
DOI: 10.1590/s0102-67202013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Pode a tela de poliéster coberta com colágeno diminuir as taxas aderências intraperitoneais na correção de hérnia incisional?

Abstract: -Background -Among meshes used in incisional hernias in open techniquerepair, the polypropylene is the most commonly used due to flexibility, cellular growth stimulation, satisfactory inflammatory response, easy manipulation and low price. However, it induces adhesions formation when in contact with the intra-abdominal contents. Aim -To evaluate the formation of adhesions after polypropylene and collagen coated polyester mesh with intraperitoneal placement. Methods -Twenty six female Wistar rats were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
(11 reference statements)
1
19
0
Order By: Relevance
“…However, surgical meshes have brought with them several complications, such as fistulas and adhesions, especially with intraperitoneal use 2,7,14,[16][17][18][19] . Postoperative adhesions to the surgical meshes may bring complications such as bowel obstruction, female infertility, postoperative abdominal pain, and repair difficulties in future surgeries 25 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, surgical meshes have brought with them several complications, such as fistulas and adhesions, especially with intraperitoneal use 2,7,14,[16][17][18][19] . Postoperative adhesions to the surgical meshes may bring complications such as bowel obstruction, female infertility, postoperative abdominal pain, and repair difficulties in future surgeries 25 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…In the United States, incisional hernia is the most common surgical complication 2,3 . Treatment options are fascial repair with tissue reapproximation and suture, or repair with the use of surgical mesh, implemented by Usher in 1958 4,5 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consecrated by its excellent biocompatibility, incorporation, maintenance of abdominal wall traction and low cost, it is associated with a high incidence of adhesions 14,22 . In experimental studies, the formation of adhesions is observed in 100% of meshes, covering from 50% to 100% of their surface 11,12,27 . The authors described the omentum as the most often involved structure, followed by the liver and the bowel.…”
Section: Discussionmentioning
confidence: 99%